Efektivitas Pelatihan Metode Penelitian Tindakan Kelas Bagi Guru SD di Kecamatan Padang Timur Kota Padang - Nellitawati Nellitawati; Aswardi Aswardi (Universitas Negeri Padang, 2017)
This training aims to help teachers, especially elementary school teachers in conducting PTK, for the improvement of learning in the future. In detail, the goal to be achieved in the first year is the teacher understands the method of classroom action research. Teachers are able to draft the PTK design and implement the PTK. Which will then acquire the copyright and publication of the manuscript on International activities. activities. In secondÂ proceed to process of designing,Â developing models and creating modules for building self-integrity programs and reducing student violence. Training activities of PTK methods for elementary school teachers are conducted in UPTD Padang Timur. The for used in lectures, training lectures, lectures, questions and answers and exercises. Before the question and answer is done, first the resource person presents the material that has been agreed upon. Then given the opportunity to participants to do question and answer and provide exercise in order to stabilize the material. The training of PTK method is done by presenting the material / theory about PTK method and followed by the drafting exercise of PTK under the guidance of the Implementation Team.